Self-enforcing environmental agreements and international trade - Thomas Eichner; Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2012)
In the basic model of the literature on international environmental agreements (IEAs) (Barrett 1994; Rubio and Ulph 2006) the number of signatories of selfenforcing IEAs does not exceed three, if non-positive emissions are ruled out. We extend that model by introducing a composite consumer good and fossil fuel that are produced and consumed in each country and traded on world markets. When signatory countries act as Stackelberg leader and emissions are positive, the size of stable IEAs may be significantly larger in our model with international trade. This would be good news if larger self-enforcing IEAs would lead to stronger reductions of total emissions. Unfortunately, the allocation of total emissions in self-enforcing IEAs turns out to be approximately the same as in the business as usual scenario independent of the number of its signatories. We also investigate the role of international trade by comparing our free-trade results with the outcome in the regime of autarky. Our autarky model turns out to coincide with the basic model of the literature alluded to above. We contribute to that literature by showing that in autarky regime the outcome of self-enforcing IEAs is also approximately the same as in business as usual.
Keywords: C72; F02; Q50; Q58; 330; international trade; self-enforcing environmental agreements; Stackelberg equilibrium; Umweltabkommen; Spieltheorie; Normbefolgung; Außenwirtschaft; Freihandel; Autarkie; Theorie